Intravesical Recurrence After Radical Nephroureterectomy of Upper Urinary Tract Urothelial Carcinoma: A Large Population-Based Investigation of Clinicopathologic Characteristics and Survival Outcomes - Wu, Jie; Xu, Pei-Hang; Luo, Wen-Jie; Dai, Bo; Shen, Yi-Jun; Ye, Ding-Wei; Wang, Yu-Chen; Zhu, Yi-Ping (Frontiers in Surgery, 2021)
Background: Of patients with upper urinary tract urothelial carcinoma (UTUC), 22%–47% developed bladder recurrence after radical nephroureterectomy. Furthermore, the benefit of surgery for UTUC-bladder cancer (BC) has not been well validated. The aim of this study was to comprehensively compared UTUC-BC with primary BC and assess the impact of standard primary BC surgical strategy on survival of patients diagnosed with UTUC-BC. Patients and methods: A total of 676 UTUC-BC patients and 197753 primary BC patients diagnosed from 2004–2016, were identified based on the SEER database. The Kaplan-Meier method and the Fine and Gray competing risks analysis were performed to assess overall survival (OS) and cancer-specific mortality (CSM). Multivariate Cox regression model and competing risks regression model were used to identify independent risk factors. Results: The baseline characteristics and survival outcomes of the two BC patient cohorts are quite different. For UTUC-BC patients, no significant difference in OS (NMIBC: p=0.88; MIBC: p=0.98) or cumulative incidence of CSM (NMIBC: p=0.12; MIBC: p=0.96) were noted for various surgical procedures. Local tumor treatment and partial cystectomy for UTUC-NMIBC patients produced lower 1-year (6.1%) and 3-year CSM (16.2%). Radical cystectomy for UTUC-MIBC patients produced lower 1-year (11.8%) but higher 3-year CSM (62.7%). Based on regression models; older age, advanced T stage, N positive disease, M positive disease, and shorter interval between UTUC and BC were identified as independent risk factors for UTUC-BC patients. Conclusion: These results highlight the significant difference among UTUC-BC and primary BC patient outcomes and suggest that current primary BC surgical guidelines are not entirely appropriate for UTUC-BC patients.